2021
DOI: 10.1007/s10654-021-00767-z
|View full text |Cite
|
Sign up to set email alerts
|

Immune age and biological age as determinants of vaccine responsiveness among elderly populations: the Human Immunomics Initiative research program

Abstract: The Human Immunomics Initiative (HII), a joint project between the Harvard T.H. Chan School of Public Health and the Human Vaccines Project (HVP), focuses on studying immunity and the predictability of immuneresponsiveness to vaccines in aging populations. This paper describes the hypotheses and methodological approaches of this new collaborative initiative. Central to our thinking is the idea that predictors of age-related non-communicable diseases are the same as predictors for infectious diseases like COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…However, it is more and more clear that this lower response is not due to the immune system of the elderly, but to the composition of vaccines. It was shown that modification of antigen concentration and especially of the adjuvant concentration and composition in flu, zoster and anti-pneumococci vaccines increases the response of the elderly immune system (titers of protective antibodies) to that similar to obtained in vaccinated young people ( Fielding and Lambert, 2015 , George and Lawrence, 2015 , Goudsmit et al, 2021 , Lal et al, 2015 ). In case of modern mRNA anti-SARS-CoV-2 vaccines, the mRNA in them is not only the information to be translated to antigenic peptide of the virus, but itself serves as an adjuvant recognized by the TLR7/8 in the cells.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is more and more clear that this lower response is not due to the immune system of the elderly, but to the composition of vaccines. It was shown that modification of antigen concentration and especially of the adjuvant concentration and composition in flu, zoster and anti-pneumococci vaccines increases the response of the elderly immune system (titers of protective antibodies) to that similar to obtained in vaccinated young people ( Fielding and Lambert, 2015 , George and Lawrence, 2015 , Goudsmit et al, 2021 , Lal et al, 2015 ). In case of modern mRNA anti-SARS-CoV-2 vaccines, the mRNA in them is not only the information to be translated to antigenic peptide of the virus, but itself serves as an adjuvant recognized by the TLR7/8 in the cells.…”
Section: Discussionmentioning
confidence: 98%
“…At the very least, this agent appears to be able to prevent anemia and thrombocytopenia in addition to neutropenia and it is reasonable that it may also prevent damage to other mitotic tissues, including the mucosa and hair follicles. It also appears to reverse the immune changes associated with aging, 72 which may prevent the efficacy of immune checkpoint inhibitors in cancer treatment. Other potential advantages of CCA include the use of a single agent to prevent multiple complications, the prevention of anemia‐related fatigue that is a major cause of disability, the avoidance of the complications of myeloid growth factors, such as pain, stem cell competition, and hematological malignancies, and the ability to administer chemotherapy at full dose intensity, even in frail and oldest patients 77‐78 …”
Section: Discussionmentioning
confidence: 99%
“…These age-related changes in the landscape of antigen presentation skew the balance between different subpopulations of lymphocytes [ 186 , 241 , 246 , 247 , 248 ]. The consequence of this is a decrease in ability of immunity to recognize “self”, “non-self”, and “altered-self”, as well as a decrease in the amplitude of the immune response [ 249 ]. The decrease in antigen presentation and subsequent decline in antigen processing impairs the ability of the immune system to recognize and destroy senescent cells in the body.…”
Section: Hscs Senility and Immune Aging As A Risk Factor For Pathologiesmentioning
confidence: 99%